Tourist Events During the COVID-19 Pandemic in Light of Polish Consumer Law - Sobiech, Jan (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
The COVID-19 pandemic brought a new perspective on travel. This applies not only to their practice but also to the legal standpoint, with all the associated consequences. This article aims to present the most relevant aspects related to the organization of package travels during the COVID-19 pandemic. This problem, in these extraordinary circumstances, is a major challenge for both tour operators and tourists. The article will raise current issues related to the cancellation of the trip from both the tour operator and the tourist, as well as matters linked with incurring additional, previously unforeseen costs. No less important, also from the legal-practical point of view, is the issue of compliance of national regulations with the EU provisions in this area. The Polish legislator’s transgression of EU law could potentially result in financial liability of the Republic of Poland not only towards EU authorities for breach of procedures but also, and perhaps most importantly, towards citizenspursuing their claims in court proceedings.